Anode layer and preparation method and application thereof
By using a resin composite containing perovskite oxide in the anode layer to form uniformly distributed pores and deposit a protective layer, the balance of the anode layer's porosity and mechanical strength is solved, the electrical performance and service life of the battery are improved, and the ability to resist carbon deposits and hydrogen sulfide poisoning is enhanced.
Patent Information
- Application Number
- CN202411978675.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The porosity and mechanical strength of the anode layer of the existing solid oxide battery are difficult to meet the requirements of high power output and good mechanical strength at the same time, and are prone to reduce electrochemical activity and stability due to carbon deposits and hydrogen sulfide poisoning.
A resin composite containing specific additives is used as the preparation raw material for the anode layer, and a perovskite oxide additive is wrapped by polymer to form a uniformly distributed circular hole, regulate the porosity and support strength, and deposit perovskite oxides in the holes to form a protective layer to improve the resistance to carbon deposits and sulfur resistance.
The synchronous improvement of the porosity and support strength of the anode layer is achieved, which improves the electrical performance and service life of the battery, and enhances the ability to resist carbon deposits and hydrogen sulfide poisoning.
Smart Images

Figure BDA0005221016130000061 
Figure BDA0005221016130000071 
Figure BDA0005221016130000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide batteries, and in particular relates to an anode layer and a preparation method and application thereof. Background Art
[0002] Solid oxide cells include solid oxide fuel cells (SOFCs) and solid oxide electrolyzers (SOECs). They are a type of highly efficient, environmentally friendly all-solid-state chemical power generation device. The anode-supported flat-plate cell uses the anode layer in the cell structure as the support for the overall structure of the single cell, and thins the electrolyte layer to reduce the internal resistance of the cell and increase the output power of the cell. It has been widely studied.
[0003] In order to ensure that the solid oxide battery has a high power output and good mechanical strength, the anode layer as a support should have appropriate porosity and support strength. During the preparation process, since the pores obtained by sintering the anode layer material itself are too few to achieve the required porosity, organic pore formers such as carbon black and starch will be added to increase the anode porosity. However, the shape of the pore former particles directly determines the morphology of the anode pores. The existing pore former particles have poor uniformity, and after sintering, irregularly sized and unevenly distributed pores are generated in the anode layer, which is not conducive to the transmission of gases in the reaction. In order to increase the porosity of the anode layer, a large amount of pore formers is often required. Excessive use of pore formers will generate a lot of heat during the sintering process, causing internal stress in the anode layer and causing the battery to crack. In addition, the increase in the porosity of the anode layer will also reduce the mechanical strength of the anode layer, and its support strength cannot be guaranteed, thereby affecting the overall electrical performance and service life of the battery. In addition, after the solid oxide battery uses hydrocarbon fuel gas to burn, it is easy to generate carbon particles inside the pores of the anode layer and deposit them on the pore walls. When operating for a long time in a high temperature environment, carbon deposits cover the nickel metal surface or cause gas channel blockage, thereby reducing the reaction efficiency. At the same time, after long-term operation, the sulfur produced by combustion accumulates and reacts with nickel to cause poisoning, which may also lead to reduced electrochemical oxidation activity and stability, and have great limitations on improving the electrical performance and service life of solid oxide batteries. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide an anode layer and a preparation method and application thereof.
[0005] The present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides an anode layer, wherein the raw materials for preparing the anode layer include the following components in percentage by mass: 20%-38% ceramic powder, 10%-20% nickel oxide powder, 30%-40% solvent, 6%-10% resin composite, 5%-10% dispersant, and the remainder is plasticizer; the resin composite includes an additive and a polymer wrapped on the surface of the additive; the additive includes a perovskite-type oxide.
[0007] The present invention uses a resin composite containing specific additives as a raw material for preparing the anode layer, which can achieve good control of the size and distribution of the pores contained in the anode layer, thereby making the anode-supported battery have good electrical performance and extended service life. The additive is wrapped with a polymer to form a resin composite and then the anode layer is prepared. On the one hand, the polymer component in the resin composite is evenly distributed inside the anode layer, and after complete decomposition by debinding, evenly distributed pores are presented. Its microscopic pore structure presents circular pores with a single shape, and the porosity and support strength are well controllable. The connectivity between the pores is good, which is conducive to gas transmission during the reaction, speeding up the reaction speed to improve the electrical performance of the battery, and avoiding the adverse effects caused by excessive use of traditional organic pore-forming agents or uncontrollable shapes. On the other hand, the perovskite oxide additives wrapped in the resin composite will be deposited on the inner wall to form a uniform protective layer while the pores are formed as the polymer gradually decomposes, thereby modifying the pores. Improve the stability of the internal structure, and meet the requirements of support strength on the basis of further improving the porosity. At the same time, the perovskite oxide deposited and covered in the pore wall makes the surface have abundant oxygen vacancies, which can provide faster charge transfer rate for redox reaction, improve electronic conductivity and catalytic activity, improve fuel gas combustion efficiency, reduce the generation of carbon particles, keep the gas passage of the hole good and will not gradually deteriorate with the extension of reaction time. In addition, the surface of the perovskite oxide additive contains lattice oxygen and adsorbed oxygen, which reacts with hydrogen sulfide gas, adsorbs a small amount of H2S in the fuel to form a sulfide layer, thereby inhibiting the reaction of hydrogen sulfide with metal nickel to cause nickel poisoning, and improving the anti-carbon deposition performance and anti-sulfur effect of the anode layer. Therefore, the present invention prepares the anode layer by adding a resin complex and rationally compounding with other components, thereby further optimizing and improving the electrical performance and service life of the anode-supported battery.
[0008] When the content of the resin composite is too low, the porosity formed by sintering is small, which reduces the pore permeability in the formed anode support layer structure, hinders the diffusion of fuel gas, and fails to meet the gas diffusion requirements. In addition, the content of the encapsulated additives is too low to achieve the anti-carbon deposition and anti-poisoning effects, making it difficult to achieve the purpose of extending the service life. When the content of the resin composite is too high, due to too many connected pores, the anode support structure collapses to a certain extent, and the support strength decreases. Excessive porosity increases the thermal expansion coefficient of the anode support layer, which does not match the electrolyte and causes the battery to crack. At the same time, too much additives are deposited inside the pores, hindering the original redox reaction and reducing the service life of the battery.
[0009] Preferably, the perovskite oxide includes at least one of a single perovskite oxide and a double perovskite oxide; the single perovskite oxide includes at least one of LaTiO3 and LaMoO3, and the double perovskite oxide includes at least one of Sr2MgMoO6 (SMM), Sr2FeMoO6 (SFM), Sr2NiMoO6 (SNM), and Sr2CoMoO6 (SCM).
[0010] Preferably, the particle size D50 of the resin composite is 5 μm-8 μm.
[0011] Preferably, the polymer includes at least one of polystyrene, polymethyl methacrylate, and polyvinyl chloride.
[0012] More preferably, the resin composite is obtained by encapsulating the additive by in-situ suspension polymerization of resin monomers into the polymer.
[0013] Preferably, the resin monomer includes at least one of styrene, methyl methacrylate and vinyl chloride.
[0014] Preferably, the mass ratio of the additive to the resin monomer is 1:(2-5); further preferably, the mass ratio of the additive to the resin monomer is 1:(2-4).
[0015] Preferably, the ceramic powder is yttria-stabilized zirconia ceramic powder; optionally, the ceramic powder includes at least one of 3YSZ, 5YSZ, 8YSZ, and 10YSZ.
[0016] Preferably, the particle size D50 of the ceramic powder is 1 μm-10 μm; more preferably, the particle size D50 of the ceramic powder is 1 μm-3 μm.
[0017] Preferably, the particle size D50 of the nickel oxide powder is 1 μm-10 μm; more preferably, the particle size D50 of the nickel oxide powder is 1 μm-3 μm.
[0018] Preferably, the solvent includes at least one of methanol, ethanol, isopropanol, toluene, ethyl acetate and acetone.
[0019] Preferably, the dispersant comprises at least one of triethanolamine, cellulose derivatives, alkyl aryl sulfonates, and polyethylene glycol (PEG).
[0020] Preferably, the plasticizer includes at least one of n-butyl phthalate (DBP) and n-octyl phthalate (DOP).
[0021] In a second aspect, the present invention provides a method for preparing the anode layer, comprising the following steps:
[0022] (1) uniformly mixing ceramic powder, nickel oxide powder, resin composite, solvent, dispersant and plasticizer according to the mass ratio to obtain an anode layer slurry;
[0023] (2) Casting the anode layer slurry obtained in step (1) into a green body, drying and sintering to obtain the anode layer.
[0024] Preferably, in step (1), the viscosity of the anode layer slurry is 2 Pa·s-4 Pa·s.
[0025] Preferably, in step (2), the thickness of the green body is 200 μm-350 μm.
[0026] Preferably, in step (2), the sintering conditions are: heating to 300°C-500°C at a heating rate of 30°C / h-60°C / h, keeping the temperature for 4h-8h, then heating to 1300°C-1500°C, and keeping the temperature for 8h-12h.
[0027] Preferably, the preparation method of the resin composite comprises the following steps: uniformly mixing the solvent, additives and silane coupling agent at 80°C-85°C, slowly dropping a mixed solution of monomer, initiator and crosslinker, reacting for 24h-36h, washing, drying and grinding to obtain the resin composite.
[0028] In a third aspect, the present invention provides an anode-supported battery, comprising the anode layer.
[0029] Preferably, the method for preparing the anode-supported battery comprises the following steps:
[0030] S1. preparing an electrolyte layer on the anode layer, obtaining a half-cell green body after lamination and hot pressing, debinding and sintering to obtain a half-cell;
[0031] S2. The half-cell obtained in step S1 is screen-printed with an LSCF cathode and sintered to obtain the anode-supported cell.
[0032] Preferably, in step S1, the electrolyte layer has a thickness of 10 μm-30 μm.
[0033] Preferably, in step S1, the binder removal sintering conditions are: heating to 300°C-500°C at a heating rate of 30°C / h-60°C / h, keeping the temperature for 4h-8h, then heating to 1300°C-1500°C, and keeping the temperature for 8h-12h.
[0034] Preferably, in step S2, the thickness of the cathode is 20 μm-50 μm; and the sintering temperature is 1000° C.-1100° C.
[0035] The present invention has the following beneficial effects:
[0036] The present invention can achieve good control of the size and distribution of the pores contained in the anode layer by using a resin composite containing specific additives, so that the anode-supported battery has excellent electrical properties and a prolonged service life. The use of polymers to wrap perovskite oxides to form a resin composite and then prepare the anode layer can, on the one hand, form evenly distributed and uniformly sized pores to improve the electrical performance of the battery, and on the other hand, the additives adhere to the surface of the pores to form a protective layer, which can further improve the stability of the structure, meet the simultaneous improvement of porosity and support strength, and can also improve the anti-carbon deposition and anti-poisoning properties of the anode layer during long-term operation, which can extend the life of the battery. DETAILED DESCRIPTION
[0037] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0038] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0039] Examples 1-12
[0040] The contents of the anode layer components of Examples 1-12 are shown in Table 1.
[0041] Comparative Examples 1-3
[0042] The contents of the anode layer components of Comparative Examples 1-3 are also shown in Table 1.
[0043] The method for preparing the anode layer of Examples 1-12 and Comparative Examples 1-3 comprises the following steps:
[0044] (1) Weigh each component according to the mass ratio described in Table 1, fully mix for 24-48 hours, and then vacuum defoam to control the viscosity of the mixed slurry to be in the range of 2-4 Pa·s to obtain an anode layer slurry;
[0045] (2) The anode layer slurry obtained in step (1) is cast into an anode layer green body with a thickness of 300 μm, and then sintered to obtain the anode layer; the specific sintering conditions are: debinding temperature 400°C, heating rate 45°C / h, holding time 6h, sintering temperature 1400°C, and holding time 10h.
[0046] In each embodiment and comparative example:
[0047] The ceramic powder is 3YSZ, and the D50 particle size is 2 μm;
[0048] The D50 particle size of the nickel oxide (NiO) powder is 2 μm;
[0049] The solvent is ethanol;
[0050] The dispersant is triethanolamine;
[0051] The plasticizer is DBP;
[0052] The component contents of the resin composites 1-11 are shown in Table 2.
[0053] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0054] Table 1 Anode layer component contents of the embodiments and comparative examples
[0055]
[0056] Table 2 Component contents and particle sizes of resin composites 1-11
[0057] Resin monomer additive Additive:monomer mass ratio D50 particle size / μm Complex 1 Styrene <![CDATA[Sr2MgMoO6]]> 1:3 5 Complex 2 Styrene <![CDATA[Sr2MgMoO6]]> 1:2 5 Complex 3 Styrene <![CDATA[Sr2MgMoO6]]> 1:4 5 Complex 4 Methyl Methacrylate <![CDATA[Sr2FeMoO6]]> 1:3 5 Complex 5 Vinyl chloride <![CDATA[Sr2NiMoO6]]> 1:3 5 Complex 6 Styrene <![CDATA[Sr2CoMoO6]]> 1:3 5 Complex 7 Styrene <![CDATA[LaTiO3]]> 1:3 5 Complex 8 Styrene <![CDATA[LaMoO3]]> 1:3 5 Complex 9 Styrene <![CDATA[Sr2MgMoO6]]> 1:3 8 Compound 10 Styrene <![CDATA[Sr2MgMoO6]]> 1:5 5 Complex 11 Styrene Styrene 1:3 5
[0058] The preparation method of resin composite 1-11 comprises the following steps: adding 50wt% ethanol-water mixed solvent in equal proportions, 10wt% additives shown in Table 2, and 5wt% silane coupling agent KH550 into a three-necked flask, heating in a water bath at 80-85°C, stirring thoroughly to make it evenly dispersed, and then adding 30wt% resin monomer shown in Table 2, 4wt% initiator BPO and 1wt% cross-linking agent 1,4-butanediol diacrylate, maintaining the heating reaction for 24-36h, so that the monomers coat the additives by suspended in-situ polymerization, and after the obtained resin composite is washed with ethanol, vacuum dried, and ground to the particle size shown in Table 2, the resin composite 1-11 is obtained.
[0059] The embodiments and comparative examples are made into anode-supported batteries, comprising the following steps:
[0060] S1. An electrolyte layer is prepared on the anode layer obtained in the embodiment and the comparative example, the electrolyte layer thickness is 10 μm, and a half-cell green body is obtained after lamination and hot pressing; the prepared half-cell green body is placed in a high-temperature furnace for debinding and sintering treatment, the debinding temperature is 400°C, the heating rate is 45°C / h, the holding time is 6h, the sintering temperature is 1400°C, the holding time is 10h, and a half-cell is obtained after sintering;
[0061] S2. The half-cell obtained in step S1 is screen-printed with an LSCF cathode and sintered with a thickness of 30 μm and a sintering temperature of 1100°C. After sintering, an anode-supported battery is obtained.
[0062] The anode layers of the embodiments and comparative examples and the corresponding batteries were used for performance testing. The items and methods of the performance testing are shown in Table 3, and the test results are shown in Table 4.
[0063] Table 3 Performance test items and methods
[0064]
[0065] Table 4 Performance test results of the anode layer and the obtained battery of the embodiment and comparative example
[0066]
[0067]
[0068] It can be seen from the results in Table 4 that the anode layer of the present invention can obtain good porosity and qualified gas permeability, so that the battery has good supporting strength and low voltage decay rate, and the electrical performance is improved while also greatly extending the service life of the battery.
[0069] By comparing Examples 1-12 and Comparative Examples 1-3, it can be seen that too much or too little addition of the resin composite will affect the performance of the battery. When the content of the resin composite is too little (Comparative Example 3), the porosity formed by sintering is too small, so that the pore permeability in the formed anode support layer structure is unqualified, and the wrapped additive content is less or the pure resin polymer without additives (Comparative Example 1) cannot achieve the anti-carbon deposition and anti-poisoning effects, the voltage decay rate is too high, and it is difficult to achieve the purpose of extending the service life; when the content of the resin composite is too large (Comparative Example 2), due to too many connected holes, the anode support structure collapses to a certain extent, the support strength is unqualified, and too much additives are deposited inside the pores to hinder the original redox reaction, the voltage decay rate is high, and the battery life is reduced.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An anode layer, characterized in that: The raw materials for preparing the anode layer include the following components in percentage by mass: 20%-38% of ceramic powder, 10%-20% of nickel oxide powder, 30%-40% of solvent, 6%-10% of resin composite, 5%-10% of dispersant, and the balance is plasticizer; the resin composite includes additives and polymers wrapped on the surface of the additives; the additives include perovskite-type oxides.
2. The anode layer according to claim 1, characterized in that The perovskite-type oxide includes at least one of a single perovskite oxide and a double perovskite oxide; the single perovskite oxide includes at least one of LaTiO3 and LaMoO3, and the double perovskite oxide includes at least one of Sr2MgMoO6, Sr2FeMoO6, Sr2NiMoO6, and Sr2CoMoO6.
3. The anode layer according to claim 1, characterized in that The particle size D50 of the resin composite is 5 μm-8 μm.
4. The anode layer according to claim 1, characterized in that The polymer includes at least one of polystyrene, polymethyl methacrylate and polyvinyl chloride.
5. The anode layer according to claim 1, characterized in that The resin compound is obtained by encapsulating the additives by in-situ polymerization of resin monomers into polymers.
6. The anode layer according to claim 5, characterized in that The mass ratio of the additive to the resin monomer is 1:(2-5).
7. The anode layer according to claim 1, characterized in that The particle size D50 of the ceramic powder is 1 μm-10 μm; and / or the particle size D50 of the nickel oxide powder is 1 μm-10 μm.
8. The anode layer according to claim 1, characterized in that The ceramic powder is yttria-stabilized zirconia ceramic powder; and / or the solvent includes at least one of methanol, ethanol, isopropanol, toluene, ethyl acetate, and acetone; and / or the dispersant includes at least one of triethanolamine, cellulose derivatives, alkyl aryl sulfonates, and polyethylene glycol; and / or the plasticizer includes at least one of n-butyl phthalate and n-octyl phthalate.
9. The method for preparing an anode layer according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) uniformly mixing ceramic powder, nickel oxide powder, resin composite, solvent, dispersant and plasticizer according to the mass ratio to obtain an anode layer slurry; (2) Casting the anode layer slurry obtained in step S1 into a green body, drying it and then sintering it to obtain the anode layer.
10. An anode-supported battery, characterized in that: The invention comprises the anode layer according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing anode-supported type solid oxide fuel battery
CN104638287A
Preparation method and application of perovskite quantum dot polymer microsphere with core-shell structure
CN112574438A
One-step low-temperature co-fired proton conductor type reversible solid oxide battery and preparation method thereof
CN114520356A
An anode on a pretreated substrate for improving redox-stablility of solid oxide fuel cell and the fabrication method thereof
EP2621006A1
Manufacture of solid electrolyte fuel cell
JP1996236137A